1998
DOI: 10.1016/s0370-2693(97)01385-3
|View full text |Cite
|
Sign up to set email alerts
|

In-medium electron-nucleon scattering

Abstract: In-medium nucleon electromagnetic form factors are calculated in the quark meson coupling model. The form factors are typically found to be suppressed as the density increases. For example, at normal nuclear density and $Q^2 \sim 0.3 { GeV}^2$, the nucleon electric form factors are reduced by approximately 8% while the magnetic form factors are reduced by only 1 - 2%. These variations are consistent with current experimental limits but should be tested by more precise experiments in the near future.Comment: 14… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 98 publications
(156 citation statements)
references
References 29 publications
13
143
0
Order By: Relevance
“…The results of the studies are consistent with the results of other solitonic approaches which include explicit vector meson degrees of freedom [13] both qualitatively and quantitatively. Our results are also consistent with the QMC model calculations [12] at a qualitative level although there are discrepancies in detail. Ideas within the present model may be useful in constructing a more consistent theory which evaluates the many-body systems and its constituents on the same footing.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The results of the studies are consistent with the results of other solitonic approaches which include explicit vector meson degrees of freedom [13] both qualitatively and quantitatively. Our results are also consistent with the QMC model calculations [12] at a qualitative level although there are discrepancies in detail. Ideas within the present model may be useful in constructing a more consistent theory which evaluates the many-body systems and its constituents on the same footing.…”
Section: Discussionsupporting
confidence: 88%
“…One can note that with the density increased q 2 dependence of G p * E falls off faster in comparison with the case in free space. The similar qualitative results have been obtained in the framework of the quark meson coupling (QMC) model [12]. However, at a quantitative level, our results are different from those in the QMC model.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…We take the density-dependence of the weak form factors generated by the QMC model [1][2][3][4]. Detailed features of the form factors and their modifications in nuclear matter used in this study are found at Ref.…”
Section: Density-dependence Weak Form Factorsmentioning
confidence: 99%
“…For the nuclear medium modification, the weak form factors with the density-dependence in the quark-meson-coupling (QMC) model was calculated by the Adelaide group [1][2][3][4]. This model successfully described various properties of hadrons in nuclear medium, finite nuclei [5], and hypernuclei [6].…”
Section: Introductionmentioning
confidence: 99%